1998
DOI: 10.1089/aid.1998.14.669
|View full text |Cite
|
Sign up to set email alerts
|

A Sudden Epidemic of HIV Type 1 among Injecting Drug Users in the Former Soviet Union: Identification of Subtype A, Subtype B, and NovelgagA/envB Recombinants

Abstract: The former Soviet Union republics have experienced an explosive human immunodeficiency virus type 1 (HIV-1) epidemic among injecting drug users (IDUs), consisting mainly of subtype A viruses originated from a point source (Bobkov et al.: AIDS Res Hum Retroviruses 1997;13:1195-1201). To determine whether new HIV-1 subtypes have entered the IDU population, 46 samples derived from IDUs in Russia (n = 39) and the Ukraine (n = 7) were genotyped by heteroduplex mobility assay (HMA). It was shown that 83% of IDU HIV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0
11

Year Published

2000
2000
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(56 citation statements)
references
References 22 publications
2
43
0
11
Order By: Relevance
“…HIV-1 infection among IDUs has another unique characteristic: a very low genetic diversity among patients. The study of HIV outbreaks among IDUs in countries of the former Soviet Union, including Belarus, Ukraine, Kaliningrad, Latvia, and Russia, showed that the mean interpatient genetic distances in the C2-V3 region of the envelope were less than 2%, but a study from Nepal showed two components, one of low diversity (2,10,16,18,19,22,23). Meanwhile, the interpatient genetic distances among HIV-1 patients with heterosexual transmission were much higher, about 8% (3,23).…”
Section: Discussionmentioning
confidence: 99%
“…HIV-1 infection among IDUs has another unique characteristic: a very low genetic diversity among patients. The study of HIV outbreaks among IDUs in countries of the former Soviet Union, including Belarus, Ukraine, Kaliningrad, Latvia, and Russia, showed that the mean interpatient genetic distances in the C2-V3 region of the envelope were less than 2%, but a study from Nepal showed two components, one of low diversity (2,10,16,18,19,22,23). Meanwhile, the interpatient genetic distances among HIV-1 patients with heterosexual transmission were much higher, about 8% (3,23).…”
Section: Discussionmentioning
confidence: 99%
“…HIV-1 isolates are classified into groups M, N, and O based on sequence identity; the vast majority of the isolates belong to group M, which is further divided into different subtypes (44). Recombination can occur between closely related strains (15,34,47,56), between isolates from different subtypes (4,5,10,33,43,49,55), or even between different HIV-1 groups (41,51). Currently, many of the circulating strains of HIV-1 are intersubtype recombinants (9,26,45,46).…”
Section: High Rates Of Hiv-1 Recombination and Their Implicationsmentioning
confidence: 99%
“…Until 1995, countries of the FSU experienced only a few hundred cases of HIV-1 infection, most of which were associated with sexual transmissions. The first outbreaks of HIV-1 among IDUs in the FSU were reported in 1995 in southern Ukraine (48), followed by rapid spread of the virus in this risk group in the Russian Federation (3,5) and its neighboring countries Belarus and the Republic of Moldova in 1996 (41,50). In 1997, the virus had spread to the Baltic region, inducing a fast-growing epidemic among IDUs in Latvia and later Estonia (2,15,64).…”
mentioning
confidence: 99%